2019
DOI: 10.1002/asia.201801732
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox‐Catalyzed Alkenylation of Benzylsulfonium Salts

Abstract: Visible light‐mediated radical alkenylation of benzylsulfonium salts was achieved by means of fac‐Ir(ppy)3 as a photocatalyst, giving allylbenzenes as products. A variety of functional groups, such as halogen, ester, and cyano, were well tolerated in this transformation. Starting benzylsulfonium salts could be readily prepared from benzyl alcohols by an acid‐mediated substitution, increasing the synthetic utility of this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…2b, B à C). Sulfonium salts, 41,42 in particular triarylsulfonium salts, 43,33 have previously been investigated as aryl radical precursors using traditional ruthenium and iridium photocatalysts, but due to their inherent structure, they display non-selective C-S bond cleavage and radical generation. Crucially, the choice of sulfonium salts formed from dibenzothiophene S-oxide (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…2b, B à C). Sulfonium salts, 41,42 in particular triarylsulfonium salts, 43,33 have previously been investigated as aryl radical precursors using traditional ruthenium and iridium photocatalysts, but due to their inherent structure, they display non-selective C-S bond cleavage and radical generation. Crucially, the choice of sulfonium salts formed from dibenzothiophene S-oxide (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Yorimitsu and co‐workers reported a visible light‐mediated radical alkenylation using benzylsulfonium salts 17 as benzyl radical precursors (Scheme ) . The reaction tolerates various functionalities on the phenyl ring of the sulfonium salt, including ortho ‐, meta ‐, and para ‐substitution, and electron‐donating/electron‐withdrawing substituents ( 19a – f ).…”
Section: Sulfonium Salts In C−c Bond Formationmentioning
confidence: 99%
“…The reaction was proposed to proceed by SET reduction of the benzylsulfonium 17 salt ( E red =−1.48 V vs . SCE) by the excited state of the photoredox catalyst ( E 1/2 IV/ * III =−1.73 V vs . SCE, Scheme ) .…”
Section: Sulfonium Salts In C−c Bond Formationmentioning
confidence: 99%
“…As discussed above, the construction of C−C bonds from various fluoroalkyl radicals generated via visible light induced C−S bond cleavage has been well studied. Nevertheless, there are only a few examples for generating alkyl radicals to construct C−C bonds through photoredox catalyzed desulfurative approaches from sulfonium salts [26–27] and sulfones, [43] respectively. In this context, in 2018, Qin group found that N ‐acyl alkylsulfinamides 213 could be used as alkyl radical precursors through visible light mediated desulfuration [44] .…”
Section: C−c Bond Formation Via C−s Bond Cleavage Enabled By Lightmentioning
confidence: 99%
“…Until 2019, Yorimitsu and co‐workers reported a visible light mediated Heck‐type radical alkenylation of benzylsulfonium salts 113 catalyzed by fac ‐Ir(ppy) 3 (Scheme 22). [26] Although a variety of functional groups were tolerated with this transformation, the sulfonium salts were only limited to benzyl ones.…”
Section: C−c Bond Formation Via C−s Bond Cleavage Enabled By Lightmentioning
confidence: 99%